Microbial interaction-induced siderophore dynamics lead to phenotypic differentiation of Staphylococcus aureus - Rajapitamahuni, Soundarya; Lyou, Eun Sun; Kang, Bo Ram; Lee, Tae Kwon (Frontiers in Cellular and Infection Microbiology, 2023)
This study investigated the impact of microbial interactions on siderophore dynamics and phenotypic differentiation of Staphylococcus aureus under iron-deficient conditions. Optimization of media demonstrated that the glycerol alanine salts medium was best suited for analyzing the dynamics of siderophore production because of its stable production of diverse siderophore types. The effects of pH and iron concentration on siderophore yield revealed a maximum yield at neutral pH and low iron concentration (10 µg). Microbial interaction studies have highlighted variations in siderophore production when different strains (Staphylococcus epidermidis, Pseudomonas aeruginosa, and Escherichia coli) are co-cultured with S. aureus. Co-culture of S. aureus with P. aeruginosa eliminated siderophore production in S. aureus, while co-culture of S. aureus with E. coli and S. epidermidis produced one or two siderophores, respectively. Raman spectroscopy revealed that microbial interactions and siderophore dynamics play a crucial role in directing the phenotypic differentiation of S. aureus, especially under iron-deficient conditions. Our results suggest that microbial interactions profoundly influence siderophore dynamics and phenotypic differentiation and that the study of these interactions could provide valuable insights for understanding microbial survival strategies in ironlimited environments.